Marshall Characteristics, Refusal Density and Abrasion Value on Hot Rolled Asphalt (HRA) Mixtures Using Laterite Stone as Replacement Aggregate - Syahairony, M.; Naibaho, Pio Ranap Tua (Universitas Ibn Khaldun Bogor, 2024)
This research examines the mechanical performance and durability of various mixtures of laterite material and crushed stone used in asphalt mixes. The materials used included AC 60-70 asphalt from Pertamina, coarse aggregate from crushed stone from a local quarry, laterite stone from a quarry in Central Kalimantan, and fine aggregate from a local quarry. The Marshall tests provided data on stability, flow, density, Volume of Voids in Mineral Aggregate (VMA), Volume of Voids in Mix (VIM), Volume Filled with Asphalt (VFWA), and Marshall Quotient (MQ). The Marshall test on the 100% laterite mixture showed that set A11-A13 had good density with moderate VMA and VIM values, as well as high stability and MQ. The slightly high flow indicated moderate elasticity. Set A21-A23 showed an increase in density with higher VMA and lower VIM, which improved stability but reduced MQ, indicating greater elasticity. Set A31-A33 showed a significant increase in stability and VFWA with higher flow, indicating high elasticity while remaining strong against load. Set A41-A43 had higher density and VFWA, slightly reduced stability, and lower MQ, indicating greater elasticity. Set A51-A53 had the highest density with very low VIM and high VFWA, showing very good cohesion but low stability and high flow, indicating significant elasticity and vulnerability to deformation. In the 50% laterite and 50% crushed stone mixture, set A11-A13 showed good density with moderate VMA and VIM, high stability and MQ, although the high flow indicated moderate elasticity. Set A21-A23 had increased density with higher VMA and lower VIM, resulting in better stability under load but reduced MQ, indicating increased elasticity. Set A31-A33 had significant stability and high VFWA with higher flow, indicating high elasticity but strong resistance to load. Set A41-A43 showed high density and VFWA with slightly reduced stability and low MQ, indicating greater elasticity. Set A51-A53 had the highest density with very low VIM and high VFWA, showing excellent cohesion but low stability and high flow, indicating significant elasticity and vulnerability to deformation. In the 100% crushed stone mixture, density ranged from 2.216 gr/cc to 2.232 gr/cc, indicating a dense and compact mixture. VMA increased from 16.70% to 19.04%, indicating an increased capacity of the mixture to hold asphalt, while VIM decreased from 5.91% to 4.05%, indicating increased density of the asphalt mix. VFWA increased from 64.65% to 78.72%, indicating improved pore filling by asphalt contributing to the cohesion of the mix. Stability ranged from 1,148.8 kg to 1,329.8 kg, indicating the mixture's ability to withstand deformation and load pressure. Stability was fairly high (1,117.84 kg) but lower MQ (291.602 kg/mm) indicated lower resistance to deformation compared to RA1-RA3. Set RC1-RC3 had the same density as RB1-RB3 (2.233 gr/cc), but higher VMA (11.64%) and larger VIM (4.37%), and lower VFWA (62.590%), indicating less efficient pore filling. The lowest stability (887.36 kg) and the lowest MQ (242.191 kg/mm) indicated suboptimal mechanical performance and higher vulnerability to deformation. In the abrasion test using the Los Angeles machine, laterite stone showed an abrasion value of 27.2%, indicating good resistance to abrasion and impact, suitable for construction applications requiring aggregates with high resistance to mechanical wear. Crushed stone experienced a mass loss of 30.9% after the abrasion test, still within the upper limit acceptable for road construction, but this aggregate is more prone to degradation when exposed to heavy traffic loads or extreme weather conditions. Aggregates with high wear tend to be more brittle, which can lead to a decrease in the quality and longevity of roads or structures built.